Data Collection and Medium Access Control Solutions for Underwater Wireless Sensor Networks - Câmara Júnior, Eduardo P. M.; Vieira, Luiz F. M.; Vieira, Marcos A. M. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2021: Anais do XXXIV Concurso de Teses e DissertaçõesDO - 10.5753/ctd.2021.15758, 2021)
Underwater wireless sensor networks (UWSNs) can enable many applications in underwater environments. They face many challenges due to the characteristics of these environments and their use of acoustic or optical communications. Here we propose solutions for two existing problems in UWSNs. One of them is CAPTAIN, a cluster-based routing solution that explores the best of each communication technology to improve data collection. We also propose UW-SEEDEX, a MAC protocol that employs random time slot schedules to allow nodes to predict each other’s transmission schedules to avoid collisions. Through simulations, we show how both proposed solutions perform better than other solutions from the literature.